PENGARUH ETIKA, KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT: Studi pada Auditor di Kantor Akuntan Publik Kota Medan - Siregar, Zuriah Hanum; Yasri, Fikri Ilmi; Simbolon, Canri; Uli Sipahutar, Tetty Tiurma (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The audit report that has been made by the auditor must have a good grade quality. Because it must be distributed to such as shareholder and the investor for the basic-decision making. Meanwhile, it must have trusted, indepedently competent element such as Kantor Akuntan Publik (KAP) to gain trust for the reportuser because beside the user, it needed by the external author for the right and accurate report and can later be used for the economic decision-making. so then, the report itself can be counted as well. However if the author has a bad reputation for their works, the result can be worse. For example the miswritten caused by the input on the accounting report. The aims of the research is to knowing the affect of auditor competency, independency and ethics towards audit qualityeither simultaneously or partially measured by the respondent. The research is using the descriptive verificated research towards causality object as for the data usingsampling data through simple random sampling which resulting 80 sample from the process. The research itself is using multiple regression-linear. It can be concluded that the auditor who works at KAP in Medan has a good competence, good independency and comprehend to apply the auditor ethics and has a good audit quality when perform their works.